The ichthyofauna of the Wilderness Lakes System, Western Cape, with particular emphasis on alien fish species and their establishment success - Olds, Alexis Amy (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2012)
Freshwater fish species have been introduced into freshwater systems around the world, primarily for aquaculture, ornamental fish trade and sport fishing. Their introduction into estuarine systems is uncommon however, instances do occur and their establishment success and impacts on these estuarine systems is not well documented. The extent of invasion by four freshwater fishes in a RAMSAR listed estuarine system, the Wilderness Lakes, Western Cape was investigated. This thesis determined the relative abundance and distribution of alien fishes in relation to the native fish biota, their establishment success in the system, what factors inhibited their establishment and whether the introduction of alien fishes negatively impacted the native fish biota. The distribution and abundance of fishes were assessed primarily using fyke nets, seine nets and gill nets in each of the lakes, interconnecting channels and the Touw Estuary. The fish fauna was made up of euryhaline marine species comprising 46%, native estuarine species comprising 18%, catadromous species comprising 7% and freshwater alien species comprising 29% of the total biomass sampled. A total of 26 species were sampled in the system, three of which were considered alien; Oreochromis mossambicus, Gambusia affinis and Cyprinus carpio, and Micropterus salmoides were not sampled but confirmed in the system. Establishment success was determined by evidence of: a sustainable breeding population, a wide distribution, abundant in the sampling area, and all size classes of fish sampled. Gambusia affinis and Oreochromis mossambicus have been recorded in the system for a minimum of 13 and 26 years respectively. They were widely distributed and highly abundant and are established in the system. Micropterus salmoides was first recorded in the system in 1985 but abundances have remained low with fish appearing to be limited to Island Lake and Langvlei. Reproduction appeared to be limited by higher salinity and these factors indicated that this was a casual species which relies on repeated introductions for population maintenance. Cyprinus carpio spawned successfully in 2010 and was widely distributed but abundances were still low with a total of 15 fish being sampled throughout the system, and was thus in the establishing phase. As these are considered freshwater alien species, the physico-chemical parameters in the estuarine environment inhibiting the establishment success of the alien fishes were investigated. Gambusia affinis and O. mossambicus were not limited by the physical environment, and while O. mossambicus cannot tolerate temperatures below 11â °C, temperatures only dropped below its tolerance for a total of two days between February 2010 and February 2011. Cyprinus carpio and M. salmoides were restricted by salinity in Rondevlei and Langvlei but could tolerate salinity in Island Lake and the Touw Estuary during closed mouth phases. While adults appeared to tolerate the salinity in the system, egg and larval development could be affected thus reducing the viability of the population. The abundance of alien fishes did not negatively impact the abundance of native fish species. The interactions between the native and alien fish biota tended towards biotic acceptance where, as alien abundance increased so did native fish abundance. The impacts of the alien fishes on the native fish biota were assessed by comparing the fish community from a study completed in 1985 to the findings of this study. From these two studies there were no apparent negative impacts on the native fish biota and the fish community composition would most likely be structured by estuarine mouth opening events.
Keywords: Introduced fishes -- South Africa -- Wilderness; Estuarine fishes -- South Africa -- Wilderness; Mozambique tilapia -- South Africa -- Wilderness; Western mosquitofish -- South Africa -- Wilderness; Carp -- South Africa -- Wilderness; Largemouth bass -- South Africa -- Wilderness; Estuarine fishes -- Effect of exotic animals on -- South Africa -- Wilderness; Fish communities -- South Africa -- Wilderness